2 µm mode-locked pulse generation using nickel metal-organic framework (Ni-MOF) coated arc-shaped fiber - Ahmad, Harith; Chiam, Joe Win; Samion, Muhamad Zharif; Ismail, Mohammad Faizal; Radzi, Zamri; Mutlu, Saliha; Sevil, Savaskan Yilmaz; Arsu, Nergis; Ortaç, Bülend; Thambiratnam, Kavintheran (Academic Press Inc., 2025)
Metal-organic framework (MOF) is an emergent material that consists of metal ions and highly porous organic ligands. In this study, we demonstrate a 2 μm all-fibre mode-locked thulium/holmium-doped fiber laser (THDFL) by utilizing a nickel-based MOF (Ni-MOF) as a saturable absorber (SA) material. For the fabrication of the SA, the material was drop-casted on an arc-shaped fiber. The SA showed a 19.98 MW/cm2 saturation intensity and an exceptionally high modulation depth of 15.3 , surpassing previously reported materials in this wavelength range. The laser output centered at 1907.66 nm with an average power reaching up to 2.057 mW. The fundamental pulse rate and width were 14.30 MHz and 1.664 ps, respectively. Consequently, the THDFL generates pulses with an energy of 175 pJ and a peak power of 105 W. Mode-locked operation proved stable as the laser was observed over 2 h and showed a signal-to-noise ratio (SNR) of about 48 dB. Notably, this work represents the first demonstration of Ni-MOF as an SA in a THDFL, opening new avenues for ultrafast fiber laser development.